Mucosaprotective action of the phytopreparation "Biotrit" at experimental hepatogenic colitis - Bocharov, A. V. (Journal of Education, Health and Sport, 2017)
Aim: To determine the role of dysbiosis in the development of colitis and to show the therapeutic and preventive effects of the phytopreparation "Biotrit" at this pathology.Materials and Methods: In rats toxic hepatitis was induced using hydrazine and intestinal dysbiosis was induced using lincomycin. In the colonic mucosa there were determined the activities of urease, lysozyme, proteases, catalase; the protein content and malondialdehyde (MDA). The degree of dysbiosis was calculated as the ratio of the relative activities of urease and lysozyme by the Levitsky method, and the antioxidant-prooxidant index API was calculated as the ratio of the catalase activity and the MDA content. Rats received the phytopreparation "Biotrit" (meal of wheat leaves) in dose 200 mg/kg daily for 21 days.Results: The combination of hepatitis with dysbiosis increases the activities of urease, proteases, the MDA content, the degree of dysbiosis and it reduces the activity of lysozyme, catalase, and API. Biotrit treatment reduce the activities urease, protease, the content MDA and degree of dysbiosis, but raise the activities lysozyme and catalase.Conclusions: Phytopreparation “Biotrit” shone mucosoprotective action on colon rats with hepategenic colitis.